2021
DOI: 10.1039/d1ra01840j
|View full text |Cite
|
Sign up to set email alerts
|

Towards the development of flexible carbon nanotube–parafilm nanocomposites and their application as bioelectrodes

Abstract: Soft, flexible and conductive interfaces, which can be used as electrode materials integrated with commercial electronic components and the human body for continuous monitoring of different analytes are in high demand in wearable electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…After acid functionalization of MWCNT, strong −OH, −C�C/−CO, and −C−N vibrations were observed at 3438, 1635, and 1050 cm −1 , respectively (Figure 1B(b)). 24,25 In 28,29 From the above-mentioned observations, it has been confirmed that the effective formations of f-MWCNT, f-MWCNT/N-(2-C 2 H 5 O) ED(CH 3 COONa) 3 , and f-MWCNT/DETA (CH 3 COOH) 5 have occurred.…”
Section: Hplc Apparatus and Separationmentioning
confidence: 62%
See 2 more Smart Citations
“…After acid functionalization of MWCNT, strong −OH, −C�C/−CO, and −C−N vibrations were observed at 3438, 1635, and 1050 cm −1 , respectively (Figure 1B(b)). 24,25 In 28,29 From the above-mentioned observations, it has been confirmed that the effective formations of f-MWCNT, f-MWCNT/N-(2-C 2 H 5 O) ED(CH 3 COONa) 3 , and f-MWCNT/DETA (CH 3 COOH) 5 have occurred.…”
Section: Hplc Apparatus and Separationmentioning
confidence: 62%
“…Also, a weak hydroxyl peak was observed at 3417 cm –1 that might be caused by moisture absorption. After acid functionalization of MWCNT, strong −OH, −CC/–CO, and −C–N vibrations were observed at 3438, 1635, and 1050 cm –1 , respectively (Figure B­(b)). , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The R a value was 8.33, the R q value was 20.20, and the difference between R a and R q was 11.87. The difference between Ra and Rq was 11 times higher than that of the PVP/MMT nanocomposites, and the roughness value (RMS) was 300 nm, which indicates the deposition of the drug and nanoclay at the polymer surface 45 . The nanoclay and drug tend to migrate to the surface of the PVP, resulting in greater roughness in certain areas 28 …”
Section: Resultsmentioning
confidence: 99%
“…The difference between Ra and Rq was 11 times higher than that of the PVP/MMT nanocomposites, and the roughness value (RMS) was 300 nm, which indicates the deposition of the drug and nanoclay at the polymer surface. 45 The nanoclay and drug tend to migrate to the surface of the PVP, resulting in greater roughness in certain areas. 28 It was possible to investigate the nanocomposite surface morphology using AFM and understand the distribution of different materials or phases, such as drugs, in the polymeric system.…”
Section: Characterization Of Pvp Nanocomposites With Lithium Carbonatementioning
confidence: 99%